Macrophage Activation Marker Soluble CD163 Is a Dynamic Marker of Liver Fibrogenesis in Human Immunodeficiency Virus/Hepatitis C Virus Coinfection. (4th June 2018) - Lidofsky, Anna; Holmes, Jacinta A; Feeney, Eoin R; Kruger, Annie J; Salloum, Shadi; Zheng, Hui; Seguin, Isabel S; Altinbas, Akif; Masia, Ricard; Corey, Kathleen E; Gustafson, Jenna L; Schaefer, Esperance A; et al.
Abstract: Background: Coinfection with human immunodeficiency virus (HIV) accelerates hepatitis C virus (HCV)–related liver fibrosis. Macrophages are triggered during both viral infections and are critical in liver inflammation/fibrogenesis. Liver fibrosis strongly associates with serum soluble CD163 (sCD163, a macrophage activation marker); comprehensive evaluation in HIV/HCV coinfection is lacking. Methods: We retrospectively analyzed sCD163 (enzyme-linked immunosorbent assay) and hepatic CD163 (immunofluorescent CD163/CD68 costaining) in patients infected with HIV/HCV, HCV, or HIV, pre– and post–antiviral therapy. Results: sCD163 was significantly higher in HIV/HCV compared to either monoinfection, and decreased following successful antiviral therapy, although did not fully normalize. In HIV/HCV, sCD163 was associated with necroinflammation, Ishak fibrosis scores, and noninvasive fibrosis scores. We observed a novel trend whereby sCD163 levels progressively increase with increasing Ishak fibrosis score, peaking at stage 4, above which levels plateaued. Periportal CD163 + macrophage frequency was also higher with increasing fibrosis score. When stratified by fibrosis stage, sCD163 levels were higher in HIV/HCV than HCV but only in individuals with mild to moderate fibrosis. Conclusions: In HIV/HCV, increasing sCD163 levels accompanied periportal CD163 + macrophage enrichment in mild to moderate fibrosis, but not in established cirrhosis, suggesting that sCD163 is a dynamic biomarker of fibrogenesis rather than accumulated fibrosis. Our findings implicate HIV-related macrophage activation in accelerated fibrosis progression in HIV/HCV coinfection. Abstract : Soluble macrophage activation marker (sCD163) and hepatic CD163 + macrophage density were compared to liver fibrosis in HIV/hepatitis C virus (HCV), HCV, HIV, and controls (4 independent cohorts). Findings implicate macrophages as dynamic mediators of fibrogenesis in the context of HIV/HCV coinfection.